2002
DOI: 10.1111/j.1574-6941.2002.tb00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial diversity in human colonic samples by 16S rDNA sequence analysis

Abstract: The bacterial species diversity of three colonic tissue samples from elderly people was investigated by sequence analysis of randomly cloned eubacterial 16S rDNA. The majority of sequences (87%) clustered within three bacterial groups: (1) Bacteroides; (2) low G+C content Gram-positives related to Clostridium coccoides (cluster XIVa); (3) Gram-positives related to Clostridium leptum (cluster IV). These groups have been shown to dominate the human faecal flora. Only 25% of sequences were closely related (>97%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
273
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(296 citation statements)
references
References 39 publications
20
273
2
1
Order By: Relevance
“…By contrast, Bacteroides sp. are among the most predominant genera of intestinal microbiota (Hold et al, 2002) and have been found to be dominant among bacteria on the ileal mucosal surface (Wang et al, 2005) and in accordance with the hypothesis of invasion of microorganisms through an ascending infection by duodenal biliary reflux (Sung et al, 1992) were observed in a high number (approximately 20%) of stent communities. This also explains the high prevalence in stent communities of acid-tolerant Streptococcus spp.…”
Section: Discussionsupporting
confidence: 74%
“…By contrast, Bacteroides sp. are among the most predominant genera of intestinal microbiota (Hold et al, 2002) and have been found to be dominant among bacteria on the ileal mucosal surface (Wang et al, 2005) and in accordance with the hypothesis of invasion of microorganisms through an ascending infection by duodenal biliary reflux (Sung et al, 1992) were observed in a high number (approximately 20%) of stent communities. This also explains the high prevalence in stent communities of acid-tolerant Streptococcus spp.…”
Section: Discussionsupporting
confidence: 74%
“…Based on 16S rRNA-targeted molecular analyses, the majority of bacteria detected in faecal samples from healthy human volunteers belong to two phyla, Bacteroidetes and Firmicutes (4)(5)(6) . The Gram-negative Bacteroidetes phylum includes the genera Bacteroides, Prevotella, Parabacteroides and Alistipes.…”
Section: Microbial Utilisation Of Dietary Polysaccharidesmentioning
confidence: 99%
“…In unfed pigs with an intracaecal perfusion of [1][2][3][4][5][6][7][8][9][10][11][12][13] ]C-butyrate, the parietal utilisation of butyrate varied from 60 to 120 mmol/min when the concentration of perfused [1][2][3][4][5][6][7][8][9][10][11][12][13] ]C-butyrate varied from 0 to 160 mmol/min (L Martin, unpublished results).…”
Section: Absorption Of Butyrate Scfa Membrane Receptor and Transportmentioning
confidence: 99%